THE USE OF A WRITE-PAIR-SQUARE STRATEGY TO IMPROVE THE STUDENTS’ ACTIVE PARTICIPATION IN WRITING DESCRIPTIVE TEXT (The Case of Tenth graders of Kesatrian 2 Semarang Senior High School in the Academic Year of 2012/2013) (Universitas Negeri Semarang, 2013)
Many problems faced by students in participating in the classroom and writing a text. This study discussed the use of write-pair-square strategy to improve the students’ active participation in writing descriptive text. The objectives of the study are to find out the implementation of write-pair-square in teaching descriptive text and to investigate the improvement of students’ participation and writing achievement after being taught by using write-pair-square strategy. The research focused on teaching of descriptive text by using write-pair-square as the strategy. The subjects are SMA Kesatrian 2 Semarang students. This study used Classroom Action Research that was carried out through a pre-test, first and second cycle activities. The result showed that the students’ progress of participation improved. The average score of pre-test was 11.27, post-test 1 was 20.13, and post-test 2 was 30.24. It also showed that students’ mastering descriptive improved. The average achievement of students’ pretest was 63.27, first cycle test was 70.23 and post test was 77.66. According to this study, I conclude that teaching descriptive text by using write-pair-square as the strategy is helpful for students. It is recommended for English teachers to use Write-pair-square as the strategy for students’ improvement of their writing skill.